Product innovation and growth: The case of integrated circuits - Marco Corsini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
A puzzling evidence stemming from the applied research on growth and innovation is that successful innovations do not appear to have a significant effect on sales growth rates, at odds with the expectation that successful innovators will prosper at the expenses of their less able competitors. The present paper tests a research hypothesis claiming that the level of observation at which applied research is typically conducted hampers the identification of a significant association between innovation and sales growth rates. Exploiting a unique and original database comprising detailed information on product innovations by leading semiconductor companies, we find components commercialized in the nearest past to positively affect the stream of corporate revenues.
Keywords: 330; Firm Growth; Product Innovation; Semiconductor industry; Innovation; Unternehmenswachstum; Halbleiterindustrie; Theorie